DEVELOPMENT OF 2D ANIMATION MEDIA AND CREATIVE SUPPORTING MEDIA FOR BASIC ENGLISH LEARNING FOR ELEMENTARY SCHOOL STUDENTS - I Komang Putra; Leli Ramdan (Journal of Aesthetics, Design, and Art Management, 2025)
Purpose: Basic English learning in elementary schools still largely uses conventional methods such as textbooks and oral explanations from teachers, making it less engaging for students and not fully suited to the learning characteristics of early childhood, which require visual and contextual media. This study aims to design 2D animation media to support basic English learning for third-grade elementary school students, specifically for the Merdeka Curriculum Unit 7 "Is it the Canteen?". Research methods: The research method used was qualitative, using observation techniques for student responses, interviews with class teachers as subject matter experts, and interviews with media experts. The design process involved pre-production, production, and post-production stages. Findings: The results of the study showed that 2D animation was able to increase student engagement, help with understanding vocabulary and interrogative sentence structure, and was in accordance with the principles of visual communication design for elementary school children. Implications: 2D animation media is considered suitable for use as an alternative learning media that is more interesting, interactive, and contextual in introducing basic English in grade 3 of elementary school.